2009
DOI: 10.1016/j.jus.2009.05.001
|View full text |Cite
|
Sign up to set email alerts
|

The role of sonoelastography in the differential diagnosis of neck nodules

Abstract: KEYWORDSTechnology assessment; Thyroid; Tumor.Abstract Sonoelastography is an imaging technique that provides information on tissue elasticity. Its use as a diagnostic procedure is based on the premise that pathological processes like cancer alter the physical characteristics of the involved tissue. Ultrasonographic studies of the neck can reveal the nonpalpable thyroid nodules, but the nature of these lesions generally has to be established on the basis of FNAB findings. In our hands, sonoelastography display… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…Recent studies demonstrated that ultrasoundbased elastography could improve detection of malignant thyroid nodules with a high sensitivity and good specificity (Lyshchik et al, 2005;Rago et al, 2007;Asteria et al, 2008;Dighe et al, 2008;Rubaltelli et al, 2009;Bojunga et al, 2010). In our study, the NPV of sonoelastography was 91% in SNs and 96% in LNs, which could be useful in determining which nodules could be safely observed without biopsy.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Recent studies demonstrated that ultrasoundbased elastography could improve detection of malignant thyroid nodules with a high sensitivity and good specificity (Lyshchik et al, 2005;Rago et al, 2007;Asteria et al, 2008;Dighe et al, 2008;Rubaltelli et al, 2009;Bojunga et al, 2010). In our study, the NPV of sonoelastography was 91% in SNs and 96% in LNs, which could be useful in determining which nodules could be safely observed without biopsy.…”
Section: Discussionsupporting
confidence: 55%
“…Pathologic changes are generally correlated with changes in tissue stiffness. Some benign nodules, such as subacute thyroiditis, nodules with coarse calcification or fibrosis, may have increased stiffness (Rago et al, 2007;Asteria et al, 2008;Hong et al, 2009;Rubaltelli et al, 2009;Bojunga et al, 2010). Thus, the false-positive results may increase, resulting in a specificity decrease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ultrasound features predictive of malignant nodules include the presence of irregular margins, marked hypoechogenicity, microcalcifications, taller-than-wide shape, intranodularvascularity (17,20,21,22,23,24). Ultrasound evaluation of the border of a thyroid nodule can be classified as well-defined or ill-defined.…”
Section: Discussionmentioning
confidence: 99%